Endometrioma of the Liver: A Case Report and Review of the Literature. (4th June 2019) - Rana, Prachi; Haghighat, Shida; Han, Hyosun
Abstract : Hepatic endometriosis is a rare form of endometriosis first described by Finkel in 1986. A thorough review of the literature revealed 28 cases of hepatic endometriosis. This unusual condition offers several diagnostic challenges due to its variable appearance on imaging and need for histologic analysis to establish a definitive diagnosis. We present a 42-year-old female initially treated for presumed hydatid cyst that was later found to be endometriosis in the liver. The case highlights the importance of considering endometriosis in the differential for a patient presenting with a solitary liver mass regardless of age and previous history of endometriosis.